Load Calculation of Limit Pair of Sun Gear on the Roadheader Cutting Reducer - Yin Ming; Li Haifei (Jixie chuandong)
During the practical application of EBZ- 260 type roadheader,the stopper plate and pin of sun gear on the cutting reducer of roadheader shall be worn seriously. According to the classical friction theory,the contact surface of limit pair of sun gear must be subject to the load. The load is one of crucial factors that influence the wear loss. In order to solve the wearing problem of stopper plate and pin,the software Solid Works is used to conduct accurate 3D modeling against the first- stage sun gear on cutting reducer of EBZ- 260 type roadheader,and the actual load condition is simulated. The Software Solid Works Simulation is used to conduct finite element statics analysis against the 3D model,so as to obtain the deformation of spline tooth of first- stage sun gear,which shall be brought into the calculation model to calculate the axial force suffered by the sun gear.Finally,other factors influencing the axial force are analyzed and the function expression of general axial force endured on the output end of the first- stage and second- stage sun gear is obtained,which shall be displayed in the MATLAB programming graph. Therefore,the determination of the wear loss causes of stopper plate and pin of sun gear is defined,and it shall provide accurate load data for further study on wearing problem.